Comparison between hepatic wedge resection and anatomic resection for colorectal liver metastases - Zorzi, Daria (2006)
Some investigators have suggested that wedge resection (WR) confers a higher incidence of positive margins and an inferior survival compared with anatomic resection (AR) of colorectal liver metastases (CLM). We sought to investigate the margin status, pattern of recurrence, and overall survival of patients with CLM treated with WR or AR. We identified 253 consecutive patients, in a multi-institutional database from 1991 to 2004, who underwent either WR or AR. WR was defined as a nonanatomic resection of the CLM, and AR was defined as single or multiple resections of one or two contiguous Couinaud segments. Clinicopathologic factors were analyzed with regard to pattern of recurrence and survival. One hundred six WRs were performed in 72 patients and 194 ARs in 181 patients. There was no difference in the rate of positive surgical margin (8.3%), overall recurrence rates, or patterns of recurrence between patients treated with WR vs. AR. Patients who had a positive surgical resection margin were more likely to recur at the surgical margin regardless of whether they underwent WR or AR. The median survival was 76.6 months for WR and 80.8 months for AR, with 5-year actuarial survival rates of 61% and 60%, respectively. AR is not superior to WR in terms of tumor clearance, pattern of recurrence, or survival. WR should remain an integral component of the surgical treatment of CLM.